Cholangio‐venous reflux of biliary contents through paracellular pathways between hepatocytes in patients with acute cholangitis. (6th April 2021) - Takada, Tadahiro; Takikawa, Hajime; Sawada, Norimasa; Higuchi, Ryota; Nagamachi, Yukiko; Isaji, Shuji; Yoshida, Masahiro; Yamamoto, Masakazu
Abstract: Background: We re‐analyzed data on cholangio‐venous reflux from a clinical study conducted prospectively on 22 patients in 1974. Method: Direct cholangiography was performed with indocyanine green (ICG) mixed into Urographin R under monitoring of intrabiliary pressure, and the participants were allocated to three groups according to whether ICG leakage into the blood, signs of infection, or both, were present. Results: The intrabiliary pressure of six patients negative for both ICG leakage and signs of infection was approximately 19.5 (median, [range 18‐22]) cmH2 O. In contrast, for the five patients positive for ICG leakage but negative for signs of infection, the intrabiliary pressure was higher (median 32.0 [range 27‐41) cmH2 O]. The 11 patients positive for both ICG leakage and signs of infection had the highest intrabiliary pressure (median 48.0 [range 33‐77] cmH2 O). Our analyses revealed that, as the intrabiliary pressure increased, the status of ICG leakage and signs of infection appeared in a stepwise fashion. Conclusion: Our findings suggest that the tight junctions sealing the bile canaliculi deteriorated with increasing intrabiliary pressure, resulting in reflux of the biliary contents into the vascular system via paracellular pathways between hepatocytes. Abstract : Highlight Takada and colleagues analyzed the results of prospective clinical verification in 22 cases to investigate the mechanism of sepsis in acute cholangitis. The tight junctions sealing the bile canaliculi deteriorated with increasing intrabiliary pressure, resulting in reflux of the biliary contents into the vascular system via paracellular pathways between hepatocytes.